ANALISIS DIPLOMASI DIGITAL NEO CULTURE TECHNOLOGY (NCT) SEBAGAI IMPLEMENTASI DIPLOMASI PUBLIK KOREA SELATAN DI INDONESIA PADA MASA PANDEMI COVID-19 (2020-2022) - Angellyca May Daniati (2023)
The South Korean government uses the Korean Wave as an instrument of soft power to spread global influence through culture. In this case, NCT also plays a role as a non-state actor who also carries out public diplomacy activities in Indonesia. The existence of the COVID-19 pandemic that has hit the world has also had an impact on the Korean Wave, especially the promotion of K-Pop music. Therefore, NCT as a non-state actor is implementing a digital diplomacy strategy to adjust the achievement of South Korean public diplomacy goals in Indonesia during the pandemic. This research will analyze how the strategies used by NCT with its digital diplomacy in order to continue to achieve the goals of South Korean's public diplomacy in Indonesia. This study uses a qualitative method which will present data in the form of facts descriptively. This research finds that NCT has implemented digital diplomacy as a strategy to achieve South Korea's public diplomacy goals, namely Shares Korean Culture, Gain global support for Korea's Policies, Strengthen public diplomacy capacity, and Promote Public-Private Partnerships.